Analisis Pelaporan dan Pertanggungjawaban Bantuan Sosial pada Laporan Keuangan Pemerintah Kota Bekasi Tahun 2019 - 2022 - Delia Rana Amanda; Petrolis Nusa Perdana; Hera Khairunnisa (Jurnal Akuntansi, Perpajakan dan Auditing, 2024)
The significant increase in the allocation of social assistance funds is a problem in Bekasi City. As the amount of funds allocated increases, the risk of misuse or waste may also increase. The purpose of this study is to analyze the policy on the budget used for social assistance and find out the regulatory basis. As well as knowing the reporting and accountability system of the realization or implementation of the social assistance budget at the Bekasi City Government in 2019 - 2022. This research uses a descriptive qualitative research design. The data used in this study are secondary data. The sample used in this study is the Bekasi City Regional Revenue and Expenditure Budget Realization Report 2019 - 2022. Analysis of documents used in this study such as: Budget Realization Report (LRA), documentation related to social assistance, and online data sources. The results showed that the policies and systems for reporting and accountability of Social Assistance (Bansos) in Bekasi City still have several weaknesses and obstacles that need to be strengthened.